Turnaround time pelayanan darah rujukan di bank darah RSUP Dr. Wahidin Sudirohusodo sebelum dan sesudah implementasi sistem informasi manajemen darah - Erika Rosaria Simbolon; Rachmawati Muhiddin; Mansyur Arif (DiscoverSys Inc., 2019)
Background: Blood Information Management System or SIMERAH is the system information which allows blood bank officers at Dr. Wahidin Sudirohusodo hospital to check blood supply in Blood Transfusion Unit. Before SIMERAH implementation, referral blood service was done by directly giving the patient’s family a blood request form to PMI without blood supply information. Referral blood service after SIMERAH implementation requires blood bank officers to order blood before referring patients to PMI. This study aims to compare Turnaround Time (TAT) of referral blood before and after SIMERAH implementation.Methods: The population of this study has been all patients receiving referral blood service to PMI since January 2017 to June 2017 (before SIMERAH implementation) and January 2018 to June 2018 (after SIMERAH implementation). Statistical analysis conducted were descriptive statistics and paired t-test.Results: The average TAT at Dr. WahidinSudirohusodo Hospital’s Blood Bank before SIMERAH implementation was 6,10 hours. The average TAT after SIMERAH implementation was 4,37 hours. There was 25,2 % decrease of average TAT after SIMERAH implementation at Dr. Wahidin Sudirohusodo Hospital’s Blood Bank. There were significant decreases of TAT in January, February, March, May, and June (p<0.05). There was a decrease of TAT in April but not statistically significant (p>0.05).Conclusion: SIMERAH was significantly decrease TAT in Dr. Wahidin Sudirohusodo Hospital’s Blood Bank.